Adaptations in the cardiac system of an Olympic downhill skiing champion: A 6-year ECG casestudy. - Eichberger, P.; Fomin, R.; Nasedkin, V.; Abubakirova, Y.; Liebich, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The contribution of the cardiac system in optimizing the training process and performance results of highly skilled skiers remains unexplored. The purpose: to observe changes in particular ECG parameters which represent adaptations in the cardiac system of an Olympic champion in response to specific training and competition loads. Methods: The study involved a 2010 Olympic champion downhill skier. Bioelectrical heart activity was recorded by ECG using Omegawave 3 technology (USA). ECGs were recorded regularly for 6 years from 2004 up to the 2010 Olympic Games, where the athlete achieved the best results of his career. Initial data contained over 800 ECG assessments. ECGs were recorded at rest using standard limb leads I, II, III (including aVR, aVL, aVF), and unipolar chest leads V2, V3R, and V6. Recording time was at least 128 sec. and took place before training or competition (5:00 to 10:00 am). A comprehensive analysis of ECG intervals and amplitude characteristics was then conducted. Heart rate variability (HRV) analysis was also used to assess the state of the autonomic nervous system (ANS). Statistical analysis was performed using SPSS 23 (USA). Results: With increased sports preparedness, changes were observed in the basic function of both the cardiac system and ANS regulatory mechanisms. Over the course of the study, a general decrease in wave amplitude R, S, T in lead V2, and S and T wave amplitude in lead V6 was observed (p<0.001). The width of the QRS complex in V6 abduction significantly increased. In standard ECG leads the width of P and T waves was significantly increased, and the amplitude of the waves Q, R, S, T decreased (p<0.001). HRV parameters showed various wavelike trends depending on the period of preparation, all within normal range. A tendency towards decreased activity of vagal regulation and increased role of the sympathetic branch of the ANS was observed. However, during the year prior to the Olympic Games, both ECG and HRV parameters showed opposite trends. In ECG leads V2 and V6, wave amplitude R, S, T increased. In HRV indices, the activity of the parasympathetic branch of the ANS and autonomous cardiac rhythm control loop increased (RMSSD, Total Power, HF), and the sympathetic branch decreased (amplitude of the mode and Tension Index). Discussion: ECG and HRV parameters are physiological markers that reflect the biological cost of forming adaptational changes in response to daily training and competition stressors. Frequent monitoring of these changes can be useful for optimizing the training process.